What Are the Obstacles to the Effectiveness of the China Supply Chain Assessment in CSR and Sustainability in Fashion Industry Relations - Zhang, Dan Feng (2016)
Summary– The purpose of this dissertation is to identify the main obstacles to the CSR and sustainability during the supply chain assessment. The case study is related to Chinese fashion industry. The literature review reveals that there are few studies related to this specific topic. Furthermore, they usually adopt a partial view which does not cover the topic of this research entirely. Secondly, in order to collect new data, 70 stakeholders were the sample of a survey and other 5 stakeholders were interviewed. Thirdly, findings of the survey and the interviews were carefully reported, also using charts, and analyzed. The outcome, by and large, confirms the narrative of the literature. On the other hand, it gives an updated and accurate portrait of Chinese fashion industry. Indeed, in recent years the Chinese labor market has started to differentiate from the other Asian economies. Finally, the findings and the suggestions of this research provide a solid base for further studies and for debating new regulations at the international level.